Vanishing bowl of local anesthetics: A lesson for sterile labeling - Narendra, P. L. (Anesth Essays Res, 2014)
It is well known that labelling is crucial in anesthetic practice. Syringe and drug preparation errors accounted for 452 (50.4%) incidents in the Australian Incident Monitoring Study database. We report a unique potential event of possible wrong route administration of medications where a bowl of local anaesthetics was mistakenly taken to the surgical trolley. This incident serves as lesson for practicing sterile labelling and identifying anaesthetic trolley.